PTH-099 Surgery for recurrent disease following right-hemicolectomy in Crohn's Disease: Analysis of Hospital Episode Statistics. (June 2019) - King, Dominic; Coupland, Ben; Dosanjh, Amandeep; Das, Ronit; Patel, Prashant; Cole, Andrew; Trudgill, Nigel
Abstract : Resectional surgery is common in patients with Crohn's Disease (CD). However, it is not curative and most develop endoscopic recurrence within a year, with the potential to develop stricturing at the anastomotic site. We examined the proportion of Crohn's patients undergoing further surgical intervention following right hemicolectomy at a national level. Methods: Hospital Episode Statistics were examined to establish a cohort of all CD subjects who had undergone right hemicolectomy between 2007–2013 in England. Subjects were followed up for 4 years and resectional surgery at the same site was analysed. Multivariable logistic regression assessed factors associated with further surgery at the same site. Results: 7491 adult patients with CD had a right hemicolectomy between 2007–2013. 45.1% were male, median age was 34 (IQR 25–44) and 88.6% were White. Most subjects had no comorbidities based on Charlson score (96.7%). Right hemicolectomies for CD increased year on year across England from 987 in 2007 to 1140 in 2013. 60% of these initial operations were elective. 9% of subjects had further resectional surgery at the same site within the 4 year follow up period. Median time to further surgery was 472 (IQR 263–945) days. 52% of subsequent surgery was performed on subjects whose initial surgery was an emergency. When factors associated with subsequent surgery were analysed, only an initial emergency right hemicolectomy was found to be associated (OR1.78 (95%CI 1.51–2.09) p<0.001) (table 1 ). If initial hemicolectomy was during an emergency admission, there was a 12.1% chance of needing surgery for recurrent disease at the same site. Conclusions: Right hemicolectomy for CD increased in England during the study period. 9% of subjects will have further surgery and an initial emergency surgical procedure was associated with the need for later surgery. Future research will focus on the indication for further surgery and examine intervention requirements over a longer follow up period.